Meningkatkan Keterampilan Siswa dalam Membaca Teks Bahasa Arab dengan Menggunakan Metode Qiro’ah - Umyanah, Yayan; Muizzudin, Mochammad (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2025)
Reading Arabic texts is a crucial skill in Arabic language instruction. However, many students still struggle to comprehend texts due to limited use of varied teaching strategies. This study aims to improve the reading skills of 10th-grade students at MAN 1 Tangerang by implementing the qirā’ah method. The research employed a Classroom Action Research (CAR) approach based on Saur Tampubolon's theory, conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. Data were collected through observation, documentation, and pre-test and post-test assessments. The results revealed a significant improvement in students' reading skills: 20% in the pre-test, increasing to 60% in the first cycle, and reaching 87% in the second cycle. These findings indicate that the qirā’ah method is effective in enhancing students' ability to read Arabic texts. The implication of this study is the importance of adopting more student-centered and contextual teaching methods to improve the quality of Arabic language education in madrasah.